2021
DOI: 10.1002/pros.24262
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer research in the 21st century; report from the 2021 Coffey‐Holden prostate cancer academy meeting

Abstract: Introduction The 2021 Coffey‐Holden Prostate Cancer Academy (CHPCA) Meeting, “Prostate Cancer Research in the 21st Century,” was held virtually, from June 24–25, 2021. Methods The CHPCA Meeting is organized by the Prostate Cancer Foundation as a unique discussion‐oriented meeting focusing on critical topics in prostate cancer research envisioned to bridge the next major advances in prostate cancer biology and treatment. The 2021 CHPCA Meeting was virtually attended by 89 investigators and included 31 talks ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 130 publications
0
4
0
Order By: Relevance
“…Stuart Holden and the late Dr. Donald Coffey, this conference aims to focus discourse and debate on critical and cutting-edge topics in prostate cancer research and related fields that have considerable potential for advancing understandings of prostate cancer biology and innovative treatment approaches. [2][3][4][5][6][7][8][9][10] The 2023 CHPCA Meeting was held from June 22 to 25, 2023 at the University of California, Los Angeles, Luskin Conference Center, in Los Angeles, CA. The Meeting was themed "Disrupting Prostate Cancer Research: Challenge Accepted."…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stuart Holden and the late Dr. Donald Coffey, this conference aims to focus discourse and debate on critical and cutting-edge topics in prostate cancer research and related fields that have considerable potential for advancing understandings of prostate cancer biology and innovative treatment approaches. [2][3][4][5][6][7][8][9][10] The 2023 CHPCA Meeting was held from June 22 to 25, 2023 at the University of California, Los Angeles, Luskin Conference Center, in Los Angeles, CA. The Meeting was themed "Disrupting Prostate Cancer Research: Challenge Accepted."…”
Section: Introductionmentioning
confidence: 99%
“…The CHPCA Meeting employs a discussion‐focused think‐tank format based on the former NCI Prouts Neck Meeting on Prostate Cancer 1 . Named in honor of prostate cancer research pioneers, Dr. Stuart Holden and the late Dr. Donald Coffey, this conference aims to focus discourse and debate on critical and cutting‐edge topics in prostate cancer research and related fields that have considerable potential for advancing understandings of prostate cancer biology and innovative treatment approaches 2–10 …”
Section: Introductionmentioning
confidence: 99%
“…Although androgen deprivation therapy and radical prostatectomy can significantly improve the prognosis of patients with prostate cancer, some still have ineffective clinical outcomes, leading to disease progression (2). Recent reports have suggested that complex molecular mechanisms contribute to prostate cancer, including factors such as hormones, neuroendocrine differentiation, epithelial-mesenchymal transition, genetic susceptibility, environmental factors, and others (3)(4)(5). A better understanding of these mechanisms will lead to better preventative strategies, enhanced diagnosis, and improved management.…”
Section: Introductionmentioning
confidence: 99%
“…The CHPCA Meeting uses a unique discussion‐focused conference format inspired by the former NCI Prouts Neck Meeting on Prostate Cancer, 1 to foster dialogue and debate surrounding the most leading‐edge and critical topics in prostate cancer research and other fields with strong potential to seed new understandings of prostate cancer biology and new treatment paradigms 2–9 . The CHPCA Meeting was named in honor of prostate cancer research pioneers, Dr. Stuart Holden and the late Dr. Donald Coffey.…”
Section: Introductionmentioning
confidence: 99%